Improvement of School Librarians' Abilities in Library Management with SLIMS Automation Software - Mustika Diana; Budhi Santoso; Teguh Teguh (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research paper aims to highlight the importance of enhancing the skills and abilities of librarians in managing information within the context of school libraries. The study specifically focuses on the use of SLIMS automation software for school library management, addressing the significance of this endeavor in the field of information technology. Method: A workshop conducted on September 18, 2021, provided hands-on training for librarians in SLIMS software, covering installation, circulation, and reporting. Post-workshop support was provided through a WhatsApp group. Practical Applications: This research benefits both librarians, who gain vital IT skills, and the education sector, where efficient library management leads to improved information access and operations. Conclusion: By improving librarian skills with SLIMS software, this study contributes to more effective school library management, benefiting students and educators alike.